HEALTH-IMPROVING FORCES OF NATURE AND HYGIENIC FACTORS - G’. M. Maxkamov (Galaxy International Interdisciplinary Research Journal, 2023)
In the process of Physical Education, air, sunlight, water are used as a means of the health-improving forces of nature. The conditions of the material and spiritual life of a person, the process of creating, living material goods in the course of his marriage can correspond to different states of an external fan. It is important to get used to it, to be ready for it. Therefore, the gift of Nature - Air, Water, sunlight-is considered to be the main means of improving human working capacity, improving health.